2023
DOI: 10.1021/acsanm.3c00765
|View full text |Cite
|
Sign up to set email alerts
|

Polyimide/Carboxylated Multi-walled Carbon Nanotube Hybrid Aerogel Fibers for Fabric Sensors: Implications for Information Acquisition and Joule Heating in Harsh Environments

Abstract: Polymeric hybrid sensors have garnered great interest in health monitoring, human−computer interaction, and soft robotics for their lightweight, flexibility, and feasible fabrication process. However, polymeric hybrid sensors suitable for harsh environments remain a considerable challenge, limiting further application. Herein, polyimide (PI)/carboxylated multi-walled carbon nanotube (c-MWCNT) hybrid aerogel fibers with a micro-porous structure were fabricated via wet-spinning and chemical thermal imidization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Ultrahigh-porous polymer aerogel fibers with thermal stability and exceptional mechanical strength, are highly sought after for applications in monitoring devices and thermal insulation, particularly in harsh environments 204,278,[293][294][295][296][297] However, the existing polymer aerogel fibers experience limitations regarding their thermal stability and mechanical properties, which restrict their potential applications. 298 To address this, Li et al 299 utilized a wet-spinning approach followed by a freeze-drying method to develop aerogel fibers based on aramid nanofibers.…”
Section: Thermal Insulation Monitoring and Responsivementioning
confidence: 99%
“…Ultrahigh-porous polymer aerogel fibers with thermal stability and exceptional mechanical strength, are highly sought after for applications in monitoring devices and thermal insulation, particularly in harsh environments 204,278,[293][294][295][296][297] However, the existing polymer aerogel fibers experience limitations regarding their thermal stability and mechanical properties, which restrict their potential applications. 298 To address this, Li et al 299 utilized a wet-spinning approach followed by a freeze-drying method to develop aerogel fibers based on aramid nanofibers.…”
Section: Thermal Insulation Monitoring and Responsivementioning
confidence: 99%
“…These mechanically strong PAI/ PU@340 aerogel fibers were remarkably superior to the already-reported aerogel fibers, such as aramid (8.1 MPa, 19.2%), 27 cellulose acetate/poly(acrylic acid)@cellulose nanofiber (CA/PAA@CNF: 5.83 MPa, 8.9%), 35 PI (11 MPa, 29.5%), and PI/carboxylated multiwalled carbon nanotube (PI/c-MWCNT: 13 MPa, 22.1%). 26,36 The intuitive comparison to illustrate the superior mechanical property of PAI/ PU@340 aerogel fibers is given by Figure 3e, and the detailed information about their mechanical performances could be found in Table S2. 27,36−40 These results declared the successful improvement of functional topoarchitected polymer networks.…”
Section: Mechanical and Fire-retardant Properties Of Topoarchitected ...mentioning
confidence: 99%
“…24,25 Liu et al's work demonstrated that polyamide acid fibers were fabricated via wet spinning first; then, heating-induced imidization was conducted to obtain PI aerogel fibers. 26 This imidization procedure makes the whole process more tedious and hard to control on the one hand; even worse, it would cause the shrinkage of fibers and destroy the designed pore structure, which plays a key role in regulating the thermal insulation performance. Another drawback for fabricating PI aerogel fibers lies in the environmental hazards of coagulation bath, such as triethylamine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation